Transgenic Mouse Model of AA Amyloidosis - Solomon, Alan (American Society for Investigative Pathology, 1999)
AA amyloidosis can be induced in mice experimentally through injection of certain chemical or biological compounds. However, the usefulness of this approach is limited by its dependence on exogenous inflammatory agents that stimulate cytokines to increase the synthesis of precursor serum amyloid A (SAA) protein and the transitory nature of the pathological fibrillar deposits. We now report that transgenic mice carrying the human interleukin 6 gene under the control of the metallothionein-I promoter had markedly increased concentrations of SAA and developed amyloid in the spleen, liver, and kidneys by 3 months of age. At the time of death about 6 months later, organs obtained from these animals had extensive amyloid deposits. This disease process was apparent radiographically using small-animal computer axial tomography and magnetic resonance imaging equipment. The AA nature of the amyloid was evidenced immunohistochemically and was unequivocally established by sequence analysis of protein extracted from the fibrils. The availability of this unique in vivo experimental model of AA amyloidosis provides the means to assess the therapeutic efficacy of agents designed to reduce or prevent the fibrillar deposits found in AA and other types of amyloid-associated disease.